Successful extracorporeal membrane oxygenation therapy as a bridge to sequential bilateral lung transplantation for a patient after severe paraquat poisoning. (21st October 2015) - Tang, Xiao; Sun, Bing; He, Hangyong; Li, Hui; Hu, Bin; Qiu, Zewu; Li, Jie; Zhang, Chunyan; Hou, Shengcai; Tong, Zhaohui; Dai, Huaping
Abstract : Context. Paraquat is a widely used herbicide that can cause severe to fatal poisoning in humans. The irreversible and rapid progression of pulmonary fibrosis associated with respiratory failure is the main cause of death in the later stages of poisoning. There are infrequent reports of successful lung transplants for cases of severe paraquat poisoning. We expect that this successful case will provide a reference for other patients in similar circumstances. Case details. A 24-year-old female was sent to the hospital approximately 2 hours after ingesting 50 ml of paraquat. She experienced rapidly aggravated pulmonary fibrosis and severe respiratory failure. On the 34th day after ingestion, she underwent intubation and invasive mechanical ventilation. The patient was evaluated for lung transplantation, and veno-venous extracorporeal membrane oxygenation (ECMO) was established as a bridge to lung transplantation on the 44th day. On the 56th day, she successfully underwent a bilateral sequential lung transplantation. Through respiratory and physical rehabilitation and nutrition support, the patient was weaned from mechanical ventilation and extubated on the 66th day. On the 80th day, she was discharged. During the 1-year follow-up, the patient was found to be in good condition, and her pulmonary function improved gradually. Conclusion: We suggest that lung transplantation may be an effective treatment in the end stages of paraquat-induced pulmonary fibrosis and consequential respiratory failure. For patients experiencing a rapid progression to a critical condition in whom lung transplantation cannot be performed immediately (e.g., while awaiting a viable donor or toxicant clearance), ECMO should be a viable bridge to lung transplantation.